“Nature’s Work:” Carolus Clusius and His Ties to the Sidney Circle - Kastnerová, Martina (American & British Studies Annual, 2024)
Philip Sidney’s European sojourn (1572-1577) was undoubtedly a formative experience, one that shaped his political and literary development. Unsurprisingly, it has received much commentary. Nevertheless, one rather neglected sphere of influence on Sidney’s education that deserves fuller attention is the coterie of high-standing and learned figures based in Central Europe, many of whom Sidney either corresponded with or met in person. This essay will consider the role of Carolus Clusius (1526-1609), a distinguished French botanist employed at the imperial court in Vienna. The influence of Clusius in Sidney’s intellectual circle and Sidney’s correspondence network will be surveyed, as well as whether Sidney’s exposure to the work of Clusius and other botanists, physicians and emblematists would have inspired Sidney’s ideas.